MENEROPONG PENERAPAN E-GOVERNMENT DI KABUPATEN SIDOARJO - Alia Kartika; Dian Iskandar (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2021)
This article is an e-government study that aims to see how the application of e-government in the Sidoarjo regency. To achieve this goal, the authors use qualitative research methods with Data collection techniques are literature studies.. The results obtained are, the local government Sidoarjo in implementing e-government using 3 relationship models, namely government to citizen, government to business, government to the employee. The implementation of e-government is supported by budget, regulation, strong institutional capacity, and the value instilled in the implementation of public servants commitment from the leadership is the main key that encourages the success of the implementation of e-government in government. In conclusion, the implementation of e-government in Sidoarjo Regency has a positive impact in organizing government affairs because of open access and making services more effective, efficient, and interactive.